Assessing migration patterns in Passerina ciris using the world’s bird collections as an aggregated resource - Linck,Ethan; Bridge,Eli S.; Duckles,Jonah M.; Navarro-Sigüenza,Adolfo G.; Rohwer,Sievert (PeerJ, 2016)
Natural history museum collections (NHCs) represent a rich and largely untapped source of data on demography and population movements. NHC specimen records can be corrected to a crude measure of collecting effort and reflect relative population densities with a method known as abundance indices. We plotted abundance index values from georeferenced NHC data in a 12-month series for the new world migratory passerine Passerina ciris across its molting and wintering range in Mexico and Central America. We illustrated a statistically significant change in abundance index values across regions and months that suggests a quasi-circular movement around its non-breeding range, and used enhanced vegetation index (EVI) analysis of remote sensing plots to demonstrate non-random association of specimen record abundance with areas of high primary productivity. We demonstrated how abundance indices from NHC specimen records can be applied to infer previously unknown migratory behavior, and be integrated with remote sensing data to provide a deeper understanding of demography and behavioral ecology across time and space.
Keywords: Migration; Behavioral ecology; Remote sensing; Ornithology; Abundance indices; Natural history museum collections; Mexico; Demography; Population density; EVI